Psychological capital research in HEI : Bibliometric analysis of current and future trends - Zhang, Li; Wider, Walton; Muhammad Ashraf, Fauzi; Jiang, Leilei; Tanucan, Jem Cloyd M.; Naces Udang, Lester (Elsevier Ltd, 2024)
This study presents a comprehensive bibliometric analysis of the literature on psychological capital (PsyCap) within higher education institutions (HEIs). Its main objective is to offer an encompassing perspective on this field's current state and potential developments. To achieve this, the study examines present research trends and predicts future directions using a bibliometric approach. A total of 412 journal articles were gathered from the Web of Science database. The analysis identifies influential publications, outlines the knowledge structure, and forecasts future trends through bibliographic coupling and co-word analyses. The bibliographic coupling revealed five distinct clusters, while the co-word analysis identified four clusters. Despite the growing significance of PsyCap research in HEIs, there remains a need for greater academic efforts to comprehend the research landscape fully. This paper provides valuable insights into the expanding area of PsyCap research within HEIs. In conclusion, the study sheds light on the extensive research conducted on PsyCap in the context of HEIs and offers insights into its potential for further growth.